Insights into the Nanostructure, Solvation, and Dynamics of Liquid Electrolytes through Small‐Angle X‐Ray Scattering. Issue 4 (18th December 2020) - Qian, Kun; Winans, Randall E.; Li, Tao
Abstract: The fundamental understanding of nanostructures of liquid electrolytes is expected to enable transformative gains in electrochemical energy storage capacities. However, the solvation structures and molecular dynamics in electrolytes are hard to probe, which limits further performance improvements in macroscopic properties such as ionic conductivity, viscosity, and stability. Small‐angle X‐ray scattering (SAXS), a non‐destructive method for nanostructures characterization in liquids, offers a unique perspective on molecular clusters, anion‐cation pairs, solvation sheath, percolating network, aggregates, and domain sizes of electrolytes. Notably, the SAXS method has excellent time‐resolution, enabling the study of molecular dynamics by operando characterization. This review focuses on the microscopic understanding of liquid electrolytes by SAXS and operando SAXS. The unique capabilities of X‐ray scattering for intra‐ and inter‐molecular relationship and nanostructure characterization of electrolytes are highlighted. Abstract : Small‐angle X‐ray scattering provides a global view of liquid electrolyte structure, which determines critical structural parameters such as solvation structure, aggregates, particle size, and arrangement.